Gender Representation in an English Textbook Published by the Ministry of Education and Culture of Indonesia - Nikmah, Azka Syifaul; Eka Sulistyawati, Anin; Yuvita, Yuvita (LPPM Universitas Pancasakti Tegal, 2022)
This study presents the representation of gender in an English textbook entitled “Bahasa Inggris SMA/MA/SMK/MAK Kelas XII”, published by the Ministry of Education and Culture of Indonesia (2018 Revised Edition). The objective of this study is to analyze the representation of gender in visual and textual forms in the textbook. Critical discourse analysis based on three dimensions of Fairclough's (2001) theory and narrative representation of Kress & Van Leeuwen's (2006) theory are applied in this study. The data were obtained from textual and visual forms based on the terms of domestic chores, role model, achievement, activities, and appearance, it also uses several terms from Porecca (1984) and Mills (2005) framework such as visibility, occupation, and noun. The result of this study showed that in representing gender in the textbook, the authors tried to promote gender equality and minimize gender stereotypes for both genders. Even though gender stereotypes still represented in the textbook, the authors tried to promote gender equality more often because gender equality representation was found in every aspect in the textbook.